2021
DOI: 10.2147/cia.s328638
|View full text |Cite
|
Sign up to set email alerts
|

The Focal Mechanical Vibration for Balance Improvement in Elderly – A Systematic Review

Abstract: Background: Aging has been associated with the progressive depletion of lean mass, reductions in muscle strength and the coordination of the lower extremities, accompanied by decreased gait assurance and balance control. Also, less balance control favors falling which is the leading cause of injury among the elderly. The aim of this systematic review is to identify and evaluate existing evidence regarding the use of focused vibration (FV) to improve balance and reduce the risk of falling during the rehabilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 52 publications
(136 reference statements)
0
8
0
1
Order By: Relevance
“…For example, it has been shown that calf muscle vibrations might improve postural control in the elderly (Toosizadeh et al, 2018). It can also improve the clinical assessment of postural control in the elderly (Paolucci et al, 2021). For instance, under vibration, some parameters of the CoP can differentiate between fallers and non-fallers (van den Hoorn et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been shown that calf muscle vibrations might improve postural control in the elderly (Toosizadeh et al, 2018). It can also improve the clinical assessment of postural control in the elderly (Paolucci et al, 2021). For instance, under vibration, some parameters of the CoP can differentiate between fallers and non-fallers (van den Hoorn et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a recent meta-analysis reported that the available studies on suprathreshold muscle tendon vibration after stroke are low in their methodological qualities and additional studies of high methodological quality are required to achieve a strong agreement concerning muscle tendon vibration intervention protocols and their recommendation in clinical settings[ 38 ]. Another systematic analysis reported that the studies that used focal mechanical suprathreshold vibration have several constraints[ 39 ]. Other studies found that prolonged exposure to high vibration is not safe and causes adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…Postural balance is the position in which an optimal distribution of body mass is achieved and that provides the body with stability and conditions for functionality in a stationary or moving position, with strategies that may include "reaction" (feedback), "anticipation" (feed-forward) or a combination of both 5 . Therefore, postural control represents a complex sensory-motor ability, whose body orientation is based on the internal representation of the body scheme derived from interactions between multiple sensorimotor processes, including peripheral and central components of the visual, somatosensory, and vestibular systems 6 .…”
Section: Introductionmentioning
confidence: 99%